PERLINDUNGAN HUKUM BAGI AHLI WARIS PEMEGANG LETTER C ATAS TANAH YANG BELUM MELAKSANAKAN PENDAFTARAN TANAH (Studi Di Desa Getas Kecamatan Tanjunganom Kabupaten Nganjuk) - Budiono, Bambang; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2024)
This study examines the legal protection for heirs of letter c holders on land who have not carried out land registration. Land is something that is very important and has a high value, because land is synonymous with running the wheel of people's lives. Ownership of land rights which has been explained by the UUPA must go through registration of ownership rights to the land so as to give rise to legal certainty over these rights. The purpose of this study is to analyze how the legal rights for heirs to land with proof of letter c have never been carried out by land registration and how land rights are transferred to heirs in connection with the obligation to register land which is still registered as evidence of letter c. This research method uses empirical legal research. The results of this study explain that where letter c is proof of the right to ownership of a land before the existence of the UUPA which regulates certificates as proof of legal land rights and has been regulated therein so that people currently use legal certificates for ownership of land rights. And the legal transfer of ownership from Letter C to a certificate has been regulated in Article 19 of the UUPA, through the National Land Agency so that the proof of ownership of the land which was originally letter c changed to form in the form of a certificate, due to the existence of the UUPA which regulates certificates as land ownership rights to make letter c has no definite legal force